KEBERHASILAN USAHA BERBASIS KOMPETENSI DAN MOTIVASI - Gemina, Dwi; Palahudin, Palahudin; Ferdiansyah, M; Gemini, Pra (Universitas Nusa Cendana, 2024)
This study aims to determine how competence and motivation affect the business performance of MSMEs partially and simultaneously in Cicurug District. The population is 105 business actors in Cicurug District in 2022. A sample of 70 individuals was obtained by purposive sampling. The primary data utilized in this research is from primary sources. Data analysis employs quantitative techniques, namely multiple linear regression analysis. The research findings indicate a simultaneous effect of competence and motivation on business success and a partial influence of each factor on business success individually. Keywords: Competence; Motivation; Business Success